THE MATTER OF DISABILITY IN THE LIGHT OF ENLIGHTENMENT IDEAS IN EUROPE OF 17–18 CENTURIES - Nazar Malaniy (Lìteraturnij Proces: Metodologìâ, Ìmena, Tendencìï, 2019)
The article reveals the leading constructs of non-normative corporeality in the context of a diachronic cut of disability studies. The dominant core is the systematization of the achievements of the Enlightenment about the problems of people with visual, hearing and speech impairments. The author analyzes the works of prominent thinkers Rene Descartes, Denis Diderot and Jean-Jacques Rousseau. Scientists have proved the possibility of successful training of people with different body. In the framework of the study the features of dependence of the sick minority from the healthy majority were outlined. Particular emphasis is placed on the theoretical, methodological and philosophical projections of disability. The possibility of applying innovative visions of the epoch for further study of this ambivalent phenomenon is noted.